The Indus and the Ganges: river basins under extreme pressure. - Sharma, Bharat R.; Amarasinghe, Upali A.; Shah, Tushaar; Bharati, Luna; Ambili, G.K.; Qureshi, Asad Sarwar; Singh, R.; Smakhtin, Vladimir U.; Xueliang Cai; Condappa, D. de; Mukherji, Aditi; Pant, Dhruba; et al. (Routledge, 2012)
The basins of the Indus and Ganges rivers cover 2.20 million km2 and are inhabited by more than a billion people. The region is under extreme pressures of population and poverty, unregulated utilization of the resources and low levels of productivity. The needs are: (1) development policies that are regionally differentiated to ensure resource sustainability and high productivity; (2) immediate development and implementation of policies for sound groundwater management and energy use; (3) improvement of the fragile food security and to broaden its base; and (4) policy changes to address land fragmentation and improved infrastructure. Meeting these needs will help to improve productivity, reduce rural poverty and improve overall human development.